Assessing the prognostic value of serum creatinine to cystatin C ratio in stage III-IV colorectal cancer: development of a nutritional prognostic scoring system - Ji, Weicheng; Zhang, Jing; Song, Jiawei; Jiang, Yu; Guo, Yajie; Liu, Shuai; Qiao, Yihuan; Pei, Yanjiang (Frontiers in Oncology, 2025)
Background and aimFor patients with stage III-IV colorectal cancer (CRC), malnutrition and poor prognosis are prevalent; however, the prognostic value of the serum creatinine to cystatin C ratio (CCR) in this setting remains uncertain. This study aims to investigate the prognostic significance of CCR and develop a nutritional prognostic scoring system based on CCR.MethodsRestricted cubic splines (RCS) were utilized to investigate the relationship between CCR and prognosis. Patients were categorized into high and low CCR groups based on RCS cut-off values and divided into quartiles (Q1 to Q4). Kaplan-Meier (KM) curves were employed for survival analysis, and multivariate Cox regression analyses were identified prognostic factors and to construct a tumor nutritional prognostic scoring system for patients. Receiver Operating Characteristic (ROC) and area under curve (AUC) were used to evaluate the scoring system.ResultsThe RCS analysis showed a linear relationship between CCR and prognosis (P = 0.76), with lower CCR levels correlating with higher hazard ratios (HR). Clinically, patients in the low CCR group exhibited poorer overall survival (OS), more advanced stages, and a higher proportion of deficient Mismatch Repair status. KM curves revealed that patients with higher CCR levels had better prognoses, with the best outcomes in the Q4 group and the worst in the Q1 group. After adjusting for confounding biases, TNM stage IV (HR = 2.34, 95% CI: 2.03 - 2.70), low CCR (HR = 1.16, 95% CI: 1.01 - 1.33) and CEA (HR = 1.17, 95% CI: 1.13 - 1.22) were identified as risk factors for prognosis, while Body Mass Index (BMI; HR = 0.98, 95% CI: 0.96 - 1.00) and albumin (HR = 0.99, 95% CI: 0.97 - 1.00) were protective factors. Finally, based on albumin levels, BMI, CEA, and CCR levels, a personalized nutritional prognostic scoring system was developed, to predict 1, 2, and 3-year OS, demonstrating good accuracy (AUC = 0.73) and calibration.ConclusionCCR levels are closely related to the prognosis of stage III-IV CRC patients, with low levels linked to malnutrition and worse outcomes. We developed a novel nutritional prognostic scoring system, which holds clinical value in predicting outcomes for patients with metastatic CRC.